Pairs in copulation of the highly dimorphic genus Pristocera Klug (Hymenoptera, Bethylidae) from Madagascar solve taxonomic problems of male-female associations - Azevedo, Celso O.; Alencar, Isabel D.c.c.; Colombo, Wesley D. (Zootaxa, 2018)
The main goal of this paper is to update the taxonomic information of the pairs of Pristocera Klug collected in Madagascar by A. Seyrig. Within this material twelve species are recognized, ten are new to science, all based on pairs collected in copulation, which are described and illustrated: P. melmani sp. nov., P. alexi sp. nov., P. martyi sp. nov., P. gloriae sp. nov., P. julieni sp. nov., P. morti sp. nov., P. mauricei sp. nov., P. makungai sp. nov., P. teetsii sp. nov. and P. zubai sp. nov.. Pristocera levicollis (Kieffer) had its female discovered, and P. cambouei Saussure stat. rev. had its lectotype designated. Sclerodermus hova Saussure is transferred back to Pristocera and considered as a junior synonym of P. cambouei. Keys for males and females to the species of Pristocera from Madagascar are provided. The Malagasy fauna of Pristocera is now represented by twelve species, all endemic to this island.